Peter Behrens and a new architecture for the twentieth century - Anderson, Stanford 1934-2016 (MIT Press, 2000)
This text looks at the work of Peter Behrens, analyzing the cultural and architectural context in which it was produced and the relation of his own house in Darmstadt to his ideal of a society where life is formed as art.
Keywords: Behrens, Peter <1868-1940>; Behrens, Peter <1868-1940> - Critique et interprétation; Behrens, Peter, 1868-1940 -- Criticism and interpretation; Behrens, Peter -- 1868-1940; Geschichte 1900-2000; Architecture - Allemagne - 20e siècle; Architecture, Modern - 20th century - Germany; Bouwkunst; Architektur; Architecture -- Germany -- 20th century; Deutschland; Hochschulschrift